KEBERSIHAN DAN KESEHATAN PADA KEPADATAN TINGGI - Glenda Wongso; Joko Priyono (Jurusan Arsitektur dan Perencanaan, 2021)
The world was shaken at the beginning of 2020 with the news of Covid-19 Virus. Indonesia is one of the countries affected by the impact, especially in Jakarta, that is still in a red zone area, which is one of the areas with the highest Covid-19 cases in Jakarta is West Pademangan in North Jakarta. West Pademangan is one of residential area with the highest population density, with a lot of slum settlements and limited public facilites to support that area. This design aims to reduce the density of buildings in order to create a distance of contact between communities in Pademangan. The presence of public facilities and green spaces also creates contact distance between communities in addition to reducing the level of density. This study used a qualitative descriptive approach, with primary data in the form of survey results and field studies as well as secondary data obtained from government data, research journals, and books. The data collection technique uses the comparative method, the overlay method, and the analysis method using the Solid-Void concept and Organic Architecture. The concept of health and hygiene in the building is inspired by a concept of a medical mask which consists of 3 layers but still can